From Islamic Education to Learning Turkish: Indonesian Muslim Gelin's Motivation to Learn Turkish - Genç, Nurbaiti Elita; Demirtaş, Zeynep (NALAR, 2024)
This article aims to explore Indonesian brides’ motivations (Gelin) to learn Turkish. This article is a qualitative study with a phenomenological approach. Data collection was conducted in January-April 2024 in Sakarya city with in-depth interviews and participant observation. There are seven informants in this study with different backgrounds. The data obtained were then analyzed using the Miles and Huberman qualitative analysis model: data reduction, data display, and conclusion. The study found that the Indonesian Gelin Muslims in Sakarya perceive Turkish as challenging to acquire, especially for Indonesians. However, there are two primary motivations for Muslim Gelin in Sakarya to learn Turkish consistently. First, to teach Islam to their children. The motivation is based on the fact that religious lessons are limited in most Turkish schools. Therefore, Gelin considers it necessary to provide additional religious lessons to her children at home, where the communication process uses Turkish. Second, nationalism motivation, which is to be able to interact socially while expressing and introducing Indonesia and its culture to the Turkish community. The findings show that religion not only mobilizes its adherents in ritual practices but can also be a vital motivating factor in foreign language acquisition.